Increased Ca(2+) content of the sarcoplasmic reticulum provides arrhythmogenic trigger source in swimming-induced rat athlete’s heart model - Gazdag, Péter (Sci Rep, 2020)
Sudden cardiac death among top athletes is very rare, however, it is 2–4 times more frequent than in the age-matched control population. In the present study, the electrophysiological consequences of long-term exercise training were investigated on Ca(2+) homeostasis and ventricular repolarization, together with the underlying alterations of ion channel expression, in a rat athlete's heart model. 12-week swimming exercise-trained and control Wistar rats were used. Electrophysiological data were obtained by using ECG, patch clamp and fluorescent optical measurements. Protein and mRNA levels were determined by the Western immunoblot and qRT-PCR techniques. Animals in the trained group exhibited significantly lower resting heart rate, higher incidence of extrasystoles and spontaneous Ca(2+) release events. The Ca(2+) content of the sarcoplasmic reticulum (SR) and the Ca(2+) transient amplitude were significantly larger in the trained group. Intensive physical training is associated with elevated SR Ca(2+) content, which could be an important part of physiological cardiac adaptation mechanism to training. However, it may also sensitize the heart for the development of spontaneous Ca(2+) release and extrasystoles. Training-associated remodeling may promote elevated incidence of life threatening arrhythmias in top athletes.